Adolescent Life Perspectives After War: Evaluation and Adaptation of the Future Expectation Scale in Uganda - Saupe, Laura B.; Gößmann, Katharina; Catani, Claudia; Neuner, Frank (Frontiers in Psychology, 2019)
The formulation of life perspectives is one of the developmental tasks of adolescence. Expectations regarding one's own future are shaped by cultural and contextual factors. However, there is little cross-cultural research that includes countries affected by war and turmoil. A Ugandan version of the Future Expectations Scale for Adolescents (FESA) was developed and evaluated with a sample of 279 Ugandan adolescents with low socioeconomic status living in rural communities affected by the Ugandan civil war (1986 – 2006). The Ugandan FESA was constructed on the basis of a combined item pool of the original Chilean and an adapted Brazilian FESA. Confirmatory factor analysis revealed that the factor structure of the original FESA did not fit the Ugandan data. Principal component analysis revealed a 3-factor solution, including the domains of children and family, work and education, and general future optimism. The final version consists of 19 items, which were deemed culturally appropriate by local focus groups. Overall, the item pool of the FESA was found useful for further studies in post-conflict societies.